2019
DOI: 10.15171/jlms.2019.39
|View full text |Cite
|
Sign up to set email alerts
|

The Photomodulation Activity of Metformin Against Oral Microbiome

Abstract: Periodontitis is one of the most common inflammatory diseases of the periodontium, which results in the inflammatory destruction of supporting structures around teeth and is closely associated with the development of systemic disease. Due to a wide variety of antibiotic resistance periodontopathic bacteria, photodynamic therapy (PDT) is a non-invasive adjunctive therapeutic modality that is capable of destroying the whole range of microbes. Metformin (Metf) is an antidiabetic drug, and recent studies suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 142 publications
(135 reference statements)
0
6
0
Order By: Relevance
“…Evidence of vasodilation and formation of collagen has also been observed. [ 54 55 56 57 58 ] The positive effects of PDT have also been documented in in vitro and study involving experimental animal models. [ 59 60 ] Although PDT shows promising results, given the problems that refractory cases show, it may not be suitable for all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of vasodilation and formation of collagen has also been observed. [ 54 55 56 57 58 ] The positive effects of PDT have also been documented in in vitro and study involving experimental animal models. [ 59 60 ] Although PDT shows promising results, given the problems that refractory cases show, it may not be suitable for all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The products produced in these reactions can cause significant damage to microorganisms and irreversibly alter their metabolic activity, resulting in the death of target cells [16]. vates photosensitizers in the presence of oxygen to produce free radicals and reactive oxygen species (ROS) that are capable of causing cell death [9,10]. Compared with other conventional antimicrobials, APDT has several strengths, including that APDT is a multitarget process, in which the spread of microbial resistance will be very rare.…”
Section: Mechanism Of Action Of Apdtmentioning
confidence: 99%
“…APDT is a minimally invasive antimicrobial approach that has been proposed as adjunctive therapy for the treatment of local infections that are resistant to antibiotics [8]. APDT is a procedure that activates photosensitizers in the presence of oxygen to produce free radicals and reactive oxygen species (ROS) that are capable of causing cell death [9,10]. Compared with other conventional antimicrobials, APDT has several strengths, including that APDT is a multitarget process, in which the spread of microbial resistance will be very rare.…”
Section: Introductionmentioning
confidence: 99%
“…Metformin is associated with reduced serum levels of C reactive protein (CRP) and monocyte release of TNF-α, IL-1β, IL-6, MCP-1, and IL-8 in pre-diabetic patients[ 171 ]. Another study reported elevated bactericidal and anti-inflammatory outcomes upon combining metformin with photodynamic therapy for the treatment of chronic resistant periodontitis[ 172 ].…”
Section: Biguanide (Metformin)mentioning
confidence: 99%